Incentive contrast in domestic dogs (Canis familiaris) - Bentosela, Mariana (2009)
Dogs (Canis familiaris) trained to receive a preferred food (dry beef liver) from an experimenter learned to maintain a longer gaze on the experimenter than dogs receiving a less preferred food (dog pellets). Dogs downshifted from dry liver to pellets rejected food more frequently than nonshifted controls. Gaze duration also decreased in downshifted dogs below the level of a group always reinforced with pellets. In addition, downshifted dogs tended to move away from the experimenter, adopting a lying down posture. This phenomenon, called successive negative contrast, has been described in analogous experiments with a variety of mammalian species, but has failed to occur in similar experiments with nonmammalian vertebrates. Unlike similar previous observations, the present data were obtained in an environment involving interspecific communication.